Mandibular Fracture Associated with a Dentigerous Cyst: Report of a Case and Literature Review - Maryam Kouhsoltani; Ali Hossein Mesgarzadeh; Monir Moradzadeh Khiavi (Tabriz University of Medical Sciences, 2015)
Background and aims. Pathological fractures are rare in the maxillofacial region and account for less than 2% of all frac-tures in this site. They are defined as fractures that take place when bone has been weakened by an underlying pathologic process. Among all pathoses, cysts (although so common in the maxillofacial region) constitute a very small part. Here we report a case of a dentigerous cyst in a 38-year-old man.The cyst was associated with a mandibular second premolar tooth and resulted in a pathologic fracture. Excision of the lesion was performed and bony union was observed after 6 months. In the literature review, only one case of dentigerous cyst causing pathologic fracture was found. In addition to the report of the present case, pathologic fractures associated with all types of odontogenic cysts (totally just 12 cases) are reviewed in this article to provide a comprehensive and detailed collection.